The Influence of the Learning Environment and Use of Blog Media on Interest in Reading History of Class VIII Students at SMPN 2 Campurdarat: Pengaruh Lingkungan Belajar Dan Penggunaan Media Blog Terhadap Minat Baca Sejarah Siswa Kelas VIII SMPN 2 Campurdarat - Suja, Imas Sukwatus; Ardhiansyah, Arvi Nurizza; Trisnantari, Hikmah Eva (The Indonesian Journal of Social Studies, 2024)
The use of appropriate learning media can certainly foster students’ interest in reading, one of the media that can be used is blog media which offers content that is relevant, easy to digest, and provides a forum for discussion. This research was conducted to determine the environment and blog media on students’ interest in reading history using quantitative descriptive methods. Research data was obtained through questionnaires, interviews and documentation which was then analyzed using multiple linier regression analysis techniques. Based on the research results, it is known that there is an influence between the learning environment and the use of blog media on the interest in reading history of class VII students at SMPN 2 Campurdarat. Based on the research results, it also appears that students’ reading culture must also be supported by complete facilities and a comfortable environment so that students are interested in reading. Keywords: Learning Environment, Media, Interest in Reading